Partial purification and characterization of pectin methylesterase from acerola (Malpighia glabra L.) - De Assis, S. A.; Martins, ABG; Guaglianoni, D. G.; Oliveira, OMMD (Amer Chemical Soc, 2002)
The enzyme pectin methylesterase (PME) is present in acerola fruit and was partially purified by gel filtration on Sephadex G-100. The results of gel filtration showed different PME isoforms. The total PME (precipitated by 70% salt saturation) and one of these isoforms (fraction from Sephadex G-100 elution) that showed a molecular mass of 15.5 +/- 1.0 kDa were studied. The optimum pH values of both forms were 9.0. The total and the partially purified PME showed that PME specific activity increases with temperature, the total acerola PME retained 13.5% of its specific activity after 90 min of incubation at 98 degreesC. The partially purified acerola (PME isoform) showed 125.5% of its specific activity after 90 min of incubation at 98 degreesC. The K-m values of the total PME and the partially purified PME isoform were 0.081 and 0.12 mg/mL, respectively. The V-max values of the total PME and the partially purified PME were 2.92 and 6.21 mumol/min/mL/mg of protein, respectively.
Keywords: pectin methylesterase; acerola; kinetic characterization; purification; isoenzymes; heat stability